Deforestation and vector-borne disease: Forest conversion favors important mosquito vectors of human pathogens - Burkett-Cadena, Nathan D.; Vittor, Amy Y. (Basic and applied ecology, 2018)
The global burden of vector-borne diseases accounts for more than 17% of infectious diseases in humans. Rapid global expansion of previously obscure pathogens, such as Zika and chikungunya viruses in recent years highlights the importance of understanding how anthropogenic changes influence emergence and spillover of vector-borne diseases. Deforestation has been identified as one anthropogenic change that influences vector-borne disease prevalence, although contrasting pictures of the effects of deforestation on vector-borne disease transmission have been reported. These conflicting findings are likely attributable to the inherent complexity of vector-borne disease systems, which involve diverse groups of vectors, hosts and pathogens, depending on geography. The current study represents a quantitative exploration of the link between deforestation and mosquitoes, the most important common constituents of vector-borne disease systems. Analysis of data compiled from published field studies for 87 mosquito species from 12 countries revealed that about half of the species (52.9%) were associated with deforested habitats. Of these species that are favored by deforestation, a much larger percentage (56.5%) are confirmed vectors of human pathogens, compared to those negatively impacted by deforestation (27.5%). Moreover, species that serve as vectors of multiple human pathogens were all favored by deforestation, including Anopheles bancroftii, Anopheles darlingi, Anopheles farauti, Anopheles funestus s.l., Anopheles gambiae s.l., Anopheles subpictus, Aedes aegypti, Aedes vigilax, Culex annulirostris, and Culex quinquefasciatus. Our quantitative analysis of vector and non-vector species, demonstrates that the net effect of deforestation favors mosquitoes that serve as vectors of human disease, while the obverse holds true for non-vectors species. These results begin to unify our understanding of the relationship between deforestation and vector mosquitoes, an important step in quantifying how land use change, specifically deforestation, affects human risk of vector-borne disease.